(untitled) (Chemical Engineering Research Bulletin, 2017)
Chemical, enzymatic or microbial activities from the surrounding environment and the food itself can cause spoilage to food products. In the meantime, the recent surge in world population, calls forfood products to be stored and delivered from one place to another place. During delivery, food products will start to deteriorate, losetheir appearance and decrease in nutritional values. Thus, the presence of food preservation methods such as heating, pickling, edible coating, drying, freezing and high-pressure processing can solve this problem by extending the food products? shelf life, stabilize their quality, maintaining their appearance and their taste. There are two categories of food preservations, the modern technology preservation method and the conventional preservation method. In the meantime, conventional food preservations usually use natural food preservatives. Meanwhile, the use of the synthetic preservative such as sulphites, benzoates, sorbates etc. for food preservation can cause certain health problems. In this light, replacing these synthetic preservatives with natural preservatives such as salt, vinegar, honey, etc. are much safer for human and environment. Furthermore, natural preservatives are easy to obtain since the sources are from plant, animal and microbes origin. This review paper focuses on preservation methodsand the natural preservatives that are suitable to be used for food preservation. Chemical Engineering Research Bulletin 19(2017) 145-153